The Entrepreneurial Activity of Chinese Migrants on the Border Areas of Russia and China at the Turn of the Centuries: the Features of “Shuttle” Migration in the Context of State and Regional Policy - Olga Zalesskaıa (Journal of Economy Culture and Society)
Russia and China have extensive border areas in the Far East. For more than 150 years, Slavic and Confucian civilizations — Russians and Chinese — have been closely involved here. The constant presence and economic activity of Chinese migrants in this region has become a specif-ic feature of the development of the border areas. In the article, the author analyzes the entrepre-neurial activity of Chinese migrants at the turn of the 20th and 21st centuries, describes in detail the socio-economic conditions and features of state and regional policies in this historical period, and highlights migration movements across the border. This paper addresses important questions: First, how were the entrepreneurial activities of Chinese migrants and their migration movements caused by the socioeconomic situation in the Russian Far East and by the ethnic characteristics of migrants? Second, how did Chinese migrants apprehend changes in state and regional policies on border areas and the opening of borders? Third, how did the border areas serve as platforms for their start-ups and do Chinese migrants consider them to be such plat-forms in the future? Through my analysis, I create a better understanding of the features of the Russian population and Chinese migrants` interaction on the border areas of the Far East, and of the perspectives for Chinese business in the peripheral regions of the conglomerate societies of Russia and China.